Analysis of challenges and barriers to the development of traditional food tourism in the restaurant industry - Rasul Abbasi; Atefeh Akbari; Kejani (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2021)
Food tourism is one of the most popular and high-income sectors of tourism in industrialized countries, both in its special domain and in contrast to other sectors. Unfortunately, Iran's tourism, restaurant, and hotel industries have failed to recognize this treasure's potential. This article aims to outline the issues and obstacles that the Iranian restaurant industry has in developing traditional food tourism. The qualitative research method and phenomenological approach were utilized in this study since it was necessary to use the lived experiences of people involved in the research topic. In-depth sampling was performed with 14 experts with experience in local food management by criterion and snowball sampling method until saturation was reached. By parenthesizing the researcher's previous knowledge, referring to the participants, and confirming them, the validity of the obtained results was determined. The findings illustrate a six-dimensional structure, including marketing barriers, low availability, poor groundwork, intra- institutional challenges, intra-union challenges, and government challenges. IntroductionIn its geographical area and relation to other sectors, food tourism is one of the developed countries most popular and lucrative goals. Traditional food is one of the best foods in different parts of the country in terms of nutritional value, availability of raw materials, freshness, free of chemical preservatives, and also cheapness. Food is not just a commodity but a cultural food embedded in the culture and customs of the local people of a region. In addition to meeting people's daily needs, food introduces tourists to food culture, and more.Materials and MethodsIn this research, a descriptive approach was used. This research is applied in terms of purpose and descriptive in terms of research method. According to the research objectives, the phenomenological method has been used as the research method, and the interview method has been used to collect data. The sampling of this research was done in the form of snowballs, and the interviewees were selected with maximum diversity from people who have experience in local food restaurant management. The sample size of this study is also determined by reaching the data saturation limit. The statistical sample is 14 people, including five women and nine men in the age group of 24 to 50 years, of which two had a bachelor's degree, seven had a master's degree, and one had a doctorate. The duration of each interview varied from 45 to 120 minutes. Semi-structured in-depth interviews were used to collect flexible data. After that, the interviews were implemented, coded, and analyzed as soon as possible to provide the necessary feedback for future interviews or adequacy and saturation. In this study, participants were first asked to explain how to choose native food and their experiences and feelings while buying and using products. The participant's answer guided the following questions, and the interview process gathered saturated information. In order to analyze, the four-step method of Bazargan et al. (2010) has been used.Discussion and ResultsUsing the phenomenological method, six main themes affecting the development of traditional food tourism were extracted, which were:"marketing barriers", "low availability", "poor groundwork", "intra-institutional challenges", "intra-union challenges", and "governance challenges". According to the participants in this study, there are marketing barriers with elements such as poor advertising, the high price of traditional food, the tendency to Western food, weak local food culture, unfamiliarity with customer tastes, poor use of cyberspace, and weak customer orientation. Previous studies have only examined the barriers to marketing in "food tourism", but the weak marketing position in "local food" has been suggested for the first time in this study. The topics of "low availability" and "poor groundwork" include local food restrictions, poor development of hospitality programs, poor local food education, and poor infrastructure with the research of some researchers are consistent. The topics of "intra- institutional challenges", "intra-union challenges", and "governance challenges" include the variables of support of guilds and government for holding food tours for cooking training, private sector investment in food tourism, and eliminating the weaknesses of restaurant management are agreeing with the results of some researches.ConclusionsThe study's findings effectively identify and understand the barriers to the development of traditional food tourism, and their elimination plays a significant role in promoting the tourism industry in Iran.